2022
DOI: 10.4102/sajip.v48i0.1932
|View full text |Cite
|
Sign up to set email alerts
|

Exploring impression management tactics within the Afrikaans Coloured culture in a formal setting

Abstract: When individuals are in the workplace, IM can be used intentionally and strategically, employees may consciously create a specific image, such as likeability, and competence amongst employees Orientation: Impression management (IM) tactics are displayed by Afrikaans Coloured individuals in formal settings. The formal setting (workplace) entails interactions with colleagues and supervisors. Research purpose: Explore and identify IM tactics displayed in the Afrikaans Coloured culture in a formal setting. Motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Thus, paying attention to one's attire and appearance is an important way to manage impressions and maintain a certain level of professionalism besides showing competence and other expected behaviours (Campbell & Taylor, 2008). For Delport et al (2022), displaying professional behaviour also meant that employees should not gossip and always endeavour to put their best foot forward. Goffman (1956) made reference to ceremonial roles, one component of which is the concern of individuals with their manner of dress because one's attire creates a sense of respect for a particular role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, paying attention to one's attire and appearance is an important way to manage impressions and maintain a certain level of professionalism besides showing competence and other expected behaviours (Campbell & Taylor, 2008). For Delport et al (2022), displaying professional behaviour also meant that employees should not gossip and always endeavour to put their best foot forward. Goffman (1956) made reference to ceremonial roles, one component of which is the concern of individuals with their manner of dress because one's attire creates a sense of respect for a particular role.…”
Section: Discussionmentioning
confidence: 99%
“…Their study was more culturally oriented, however, leaving room for a more organisationally contextualised study. Delport, Mtshelwane, and Rossouw (2022) took up this challenge by exploring the impression management strategies employed by Afrikaans mixed-race individuals in the work setting. Findings demonstrated that they use impression management strategies such as working hard, expressing opinions and displaying professional behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Other empirical investigations concentrated on the effect, impact, and influence of impression management on other criterion variables other than employee contextual performance [28,29]. Again, just recently, McGowan & Sekaja [30] and Delport et al [31] examined the effect of impression management tactics on other variables that are different from employee contextual performance. This has created a lacuna in impression management research.…”
Section: Impression Management and Employee Contextual Performance Inmentioning
confidence: 99%
“…McGowan & Sekaja [30] identified the impression management strategies used by organizational psychology interns in South African firms and, found that they employ ingratiation, exemplification, self-promotion, rendering favours, professionalism, conformity, openness to learning, and strategic relationship building. Delport et al [31] explored the impression management tactics of Afrikaans coloured managers in South Africa and discovered that coloured Afrikaans managers used different impression management tactics to influence their subordinates. Research has shown that managers who used exemplification, ingratiation, and supplication tactics exhibited significant transformational leadership behaviours whereas those who adopted self-promoting and intimidating behaviours had low transformational leadership behaviours [78].…”
Section: -3-impression Management and Employee Contextual Performancementioning
confidence: 99%